Investigation into the formation, blockage and dissociation of cyclopentane hydrate in a visual flow loop. (1st January 2022) - Liu, Zhiming; Li, Yuxing; Wang, Wuchang; Song, Guangchun; Ning, Yuanxing; Liu, Xiang; Zhang, Jialu
Highlights: CP hydrate formation, blockage, and dissociation in a visual flow loop were investigated. Micro-morphology of the hydrate formation on the wall was intuitively exhibited. Effect of CP-water volume ratios and flow rates on hydrate formation were studied. Different dissociation patterns were observed adopting different temperature-rising protocols. Mechanism of hydrate bulges formed on hydrate deposition was proposed. Abstract: Hydrate formation and deposition are critical flow assurance risk for the normal operation and management of the pipelines, so the macro- and micro-morphologies of the forming and dissolving hydrate in the flow loop are of great significance to clarify the mechanisms of the hydrate deposition and blockage under the flowing conditions. In this work, a self-designed flow loop and a micro-observation device for the hydrate formation and dissociation were constructed. With different CP-water volume ratios and initial flow rates, the process of CP hydrate formation, blockage, and dissociation in the half and full pipe flow was studied respectively. It was found that in the flow loop, with the increase of the water volume and the flow rate of the CP-water mixed fluid, a delay of the hydrate blockage was observed both in the half and full pipe flow, and the blocking phenomena varied with the initial volume ratio and the flow rate; the micro-morphologies of the hydrate formation on the wall was intuitively exhibited by the videos captured by the high-speed camera; In the half pipe flow, hydrate deposition was observed on the pipe wall in the air space, and the diffusion of the CP gas and the moisture resulted in the bulges formed on the hydrate deposition; In the process of hydrate dissociation, adopting different temperature-rising protocols, gas bubbles was appeared only in the hydrate slurry when the temperature was increased at a lower rate, and the reasons for the distinction was finally clarified by the micro-morphologies of the dissolving hydrate. This work provides insights on the hydrate formation and dissociation under the flowing conditions, which is also helpful to clarify mechanisms of the hydrate deposition and blockage in pipelines and thereby facilitates the flow assurance in the oil-gas transportation pipelines.